Future trends of quality engineering and quality management implementation and practices - Farhad Nejadi, 1984-; Sha'ri Mohd. Yusuf, supervisor; Fakulti Kejuruteraan Mekanikal (2014)
Thesis (Sarjana Kejuruteraan (Kejuruteraan Industri)) - Universiti Teknologi Malaysia, 2014